A case with intravascular large B cell lymphoma who was presented with fever of unknown origin, edema and generalized telangiectesia - Sevindik, Ömür; Erol, Vedat; Mutlu, Yaşa; Balık Aydın, Berrin; Çakır, Aslı (Wiley, 2021)
[Abstract Not Available]
Keywords: Generalized Telangiectesia; Unknown Origin; Edema